Russian-Ukrainian war impacts the total environment - Pereira, Paulo; Bašić, Ferdo; Bogunovic, Igor; Barcelo, Damia (The Science of the total environment, 2022)
The Russian-Ukrainian war triggered a tsunami that dramatically impacted the world economy, geopolitics, and food security. Due to the extreme humanitarian situation, the effects on the environment have been overlooked. However, due to the intense fighting, the impacts will be dramatic and produce an environmental disaster. The war is already affecting areas beyond Ukraine (explosions in Russia and Moldova territory). This discussion paper aims to shed light on the potential effect of this vast conflict on the ecosystems and their services. Although the war is still ongoing, there is evidence of severe air pollution and greenhouse gas emissions resulting from the intense fights. Also, warfare activities were conducted in the vicinity of the Zaporizhzhia nuclear power plant (the biggest in Europe) and Chernobyl, increasing the fear of radiation leaks. The biodiversity is being drastically affected due to intense deforestation and habitat destruction with potential implications for wildlife. Bombing, trench and tunnel excavations will likely negatively impact soil degradation and landscape morphology. This assumes particular importance since Ukraine has some of the most fertile soils globally (Chernozem), affecting food production. Water availability and quality are likely to be affected due to infrastructure destruction and the transport of pollutants to water reserves. The ecosystem services supplied will likely be strongly damaged since deforestation will decrease the capacity of the ecosystems to regulate air pollution or climate. Soil degradation will hamper food production, and landscape aesthetics, cultural heritage and social cohesion destruction drastically affects cultural services. Finally, the impacts on human health are already tremendous. However, it can be even higher due to exposure to high levels of contamination and sanitary conditions degradation. The war is still ongoing, and there is considerable uncertainty regarding the impacts. However, we may expect a dramatic effect on the total environment. [Display omitted]